Clinical case of acute hepatitis caused by parvovirus B 19 - K. V. Sobolevskiy; I. A. Otmakhova; B. Ya. Gadirova; Zh. E. Zueva (Журнал инфектологии)
Parvovirus infection is one of the most widespread infectious diseases in the world. Parvovirus В19 can cause a wide range of clinical manifestations with possible long-term viral persistence. Infectious erythema, arthropathy, fetal infection, and blood cell aplasia are the most common manifestations of parvovirus infection. A case of diagnosis and treatment of a rare variant of parvovirus B19 infection that occurred as acute hepatitis is presented.